Bank Customer Loyalty at Post-Implementation of Automatic Exchange of Information (AEOI) in Indonesia - Sukirno Sukirno; Nabella Putri Hari Pratiwi; Abolfazl Amanollanejad (Universitas Ahmad Dahlan, 2021)
Introduction: Many studies have been conducted massively in around the globe, nevertheless still no study conducted on exploring the impact of banking industries’ AEOI adoption on customer loyalty, trust, commitment and satisfaction. Purpose: The purpose of this paper is to investigate the effect of trust, commitment, and satisfaction on customer loyalty and, in turn, the indirect effect of satisfaction on customer loyalty at post-implementation of the Automatic Exchange of Information (AEOI). Methodology: A model is advanced and tested using partial least squares path modeling (PLS-SEM) and data were collected from a sample of 200 banking industry customers in Indonesia. Findings: The results indicate significant and positive relationships among trust, commitment, satisfaction, and customer loyalty. Moreover, it is found that satisfaction has an indirect effect in relation to trust, commitment, and customer loyalty. The findings and limitations are discussed and recommendations for the policy makers and researchers are also provided. Paper Type: Research Article